Responsibility of Foundation Management towards Third Parties Based on Law Number 28 of 2004 - Aji, Ahmad Mukri; Yunus, Nur Rohim; Mukri, Syarifah Gustiawati (SALAM: Jurnal Sosial dan Budaya Syar-i, 2024)
A foundation as a non-profit legal entity has a vital role in carrying out social, religious, and humanitarian activities. However, many foundations carry out business activities to support operational costs. This has raised debates regarding the limits of business activities permitted for foundations, especially after the enactment of Law Number 28 of 2004 concerning Amendments to Law Number 16 of 2001 concerning Foundations. This study aims to analyse legal provisions related to the limits of foundation business activities and evaluate the legal consequences for foundations and administrators who exceed the limits of business activities stipulated in laws and regulations. The research method used is normative legal research with a statutory and conceptual approach. The data sources include laws, legal documents, jurisprudence, and relevant scientific literature. The analysis of legal norms and foundation management practices related to business activities was conducted qualitatively. The study results indicate that Law No. 28 of 2004 explicitly limits foundation business activities only through business entities established by or owned by foundations, as long as the results are used to achieve the foundation's goals. Violating these provisions, such as conducting business activities directly without going through a business entity, can result in legal consequences, including freezing or dissolution of the foundation and personal liability of administrators abusing their authority.Keywords: Foundation; Business Activities; Legal Liability; Administrators, Law No. 28 of 2004.